IMPLEMENTATION OF AHP METHOD FOR THE SELECTION OF THE BEST SCHOOLS IN MEDAN CITY BASED ON THE WEBSITE - Syarifah Fadillah Rezky; Rita Hamdani; Siti Julianti Siregar (Sean Institute, 2021)
In selecting the best school for prospective students or those who will continue their education. There are many criteria that must be seen from the number of schools in the city of Medan, which is one of the factors determining the quality of the school. Because they only use newspapers and brochures, many prospective students are confused or hesitant in deciding which school to attend. Many schools are often not in accordance with the information contained in the media newspapers and brochures, this of course can be detrimental to prospective students / students who want to enter the school. Thus many prospective students or guardians of students feel doubt in determining which school to choose. Based on previous research regarding the selection of the best schools in journals,